The Effect of Deep Breath Relaxation Therapy on Pain Intensity in Post Patients Fracture Surgery in Seruni Room of dr. M. Yunus Hospital Bengkulu - Devi Listiana; Pawiliyah Pawiliyah; Fatma Hidayah (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
The condition of postoperative femur patients experiences pain around the incision which is an unpleasant sensory and emotional experience accompanied by potential and actual tissue damage. This study aims to study the effect of deep breathing relaxation therapy on pain intensity in post fracture surgery patients in seruni room of dr. M. Yunus Hospital Bengkulu. The design used in this study was Pre-Experimental used The One Group Pretest Postest Design. The population of this study was all postoperative fracture patients after 4 hours in seruni room of dr. M. Yunus Hospital Bengkulu. Sampling in this study used Accidental Sampling techniques as many as 30 people. This study used primary data. Data analysis was done by univariate, bivariate with Chi-Square Test. The results of the study were obtained from 30 postoperative fracture patients before the respiratory relaxation technique was obtained. The minimum pain scale was 3, the maximum pain scale was 9, the average pain scale was 5.80 with a standard deviation of 1.518, after breathing relaxation techniques were obtained a minimum pain scale of 2, the maximum pain scale was 8, the average pain scale was 4.97 with a standard deviation of 1.520; There was an effect of deep breathing relaxation therapy on pain intensity in post fracture surgery patients in seruni room of dr. M. Yunus Hospital Bengkulu. It was expected that health care workers can provide health education to patients about the benefits of deep breathing relaxation therapy as non-pharmacological therapy in patients post fracture surgery. Keywords: Breathing Relaxation Therapy, Pain Intensity, Post Operation Patient